Recent Progress Towards a Gonococcal Vaccine - Maurakis, Stavros A.; Cornelissen, Cynthia Nau (Frontiers in Cellular and Infection Microbiology, 2022)
Gonorrhea is a global health concern. Its etiological agent, Neisseria gonorrhoeae, rapidly acquires antimicrobial resistance and does not confer protective immunity as a consequence of infection. Attempts to generate an effective vaccine for gonorrhea have thus far been unsuccessful, as many structures on the bacterial envelope have the propensity to rapidly change, thus complicating recognition by the human immune system. In response to recent efforts from global health authorities to spur the efforts towards development of a vaccine, several new and promising steps have been made towards this goal, aided by advancements in computational epitope identification and prediction methods. Here, we provide a short review of recent progress towards a viable gonococcal vaccine and discuss a few of the tools that may be important in furthering these efforts.